Cross Fertilization of Ideas between Indigenous Knowledge and Western Science: Navigating the Complexity in Science Lessons - Fredrick Simataa Simasiku (Journal of Research in Education and Pedagogy, 2025)
Learners find it difficult during science lessons when they are asked to relate their indigenous knowledge to Western science, not only that they do not know that they might know it in their indigenous language, but it difficult for them to translate it into the language of teaching and learning (LoTL). The complexity of the indigenous language in science lessons hinders the integration of IK in science lessons. The aim of the study was to investigate the complexity of indigenous knowledge in science lessons that are taught in English when the teacher includes learners’ lived experiences in science lessons. Social constructivism theory was used as the lens to analyse the data. The study employs the Dialogical Argumentation Instructional Model (DAIM) and Contiguity Argumentation Theory (CAT) as analytical tools to analyze the data obtained from the learners during science lessons. The study involved Grade 9 learners taught the topic on acids and bases in a rural school in the Ohangwena region. The data were generated using lesson observation and focus group interviews with learners. The major findings of this study show that learners are loaded with indigenous knowledge before they enter the science classroom, and teachers need to use this knowledge to enhance the conceptual understanding of learners in science lessons. The study also shows that using argumentation as a teaching model helped learners to reflect back and engage their indigenous knowledge in science lessons. However, some learners were not able to cross-fertilize the indigenous knowledge into scientific knowledge due to a lack of terminology in English. Thus, the study recommends that teachers need to be trained on how to integrate indigenous knowledge into their lessons.